2021
DOI: 10.1108/jhti-03-2021-0061
|View full text |Cite
|
Sign up to set email alerts
|

How do executive pay and its gap with employee pay influence corporate performance? Evidence from Thailand tourism listed companies

Abstract: PurposeThe authors investigate how executive pay and its gap with employee pay influence the performance of Thailand tourism listed companies.Design/methodology/approachThe authors manually collect data on the executives' and employees' remunerations for Thailand tourism listed companies and use the data for the authors’ OLS regression analysis. To check the robustness of the results to potential endogeneity issues, the authors employ the two-stage least-squares regression analysis and the impact threshold for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Pay is one of the most controversial areas of well-being research (Alieva and Powell, 2022;Ferry et al, 2023;Massingham and Tam, 2015;Valaei and Rezaei, 2016), but many researchers agree that fair and competitive pay systems contribute to organisational commitment (Dargahi and Veysi, 2021;Valaei and Rezaei, 2016). Research on executive pay strategies has found that rewarding managers appropriately improves organisational performance in the short term and reduces the likelihood of adverse corporate performance in the long term (Ferry et al, 2023). This is particularly noticeable in crises, when it may be necessary to modify expectations related to the standard of living (Z eman et al, 2021).…”
Section: Dimensions Of Well-being At Workmentioning
confidence: 99%
“…Pay is one of the most controversial areas of well-being research (Alieva and Powell, 2022;Ferry et al, 2023;Massingham and Tam, 2015;Valaei and Rezaei, 2016), but many researchers agree that fair and competitive pay systems contribute to organisational commitment (Dargahi and Veysi, 2021;Valaei and Rezaei, 2016). Research on executive pay strategies has found that rewarding managers appropriately improves organisational performance in the short term and reduces the likelihood of adverse corporate performance in the long term (Ferry et al, 2023). This is particularly noticeable in crises, when it may be necessary to modify expectations related to the standard of living (Z eman et al, 2021).…”
Section: Dimensions Of Well-being At Workmentioning
confidence: 99%
“…Following the literature (Ferry et al, 2023; Kim et al, 2018; Ullah et al, 2019), we consider Tobin’s Q as a market-based measure of firm performance for the robustness test. The findings shown in Table 7 confirm the previous results reported in Table 3, indicating that R&D_S , R&D_A , and R&D_C adversely influence firm performance.…”
Section: Empirical Findingsmentioning
confidence: 99%
“…Testing Robustness Using Tobin's Q as a Dependent Variable. Following the literature (Ferry et al, 2023;Kim et al, 2018;Ullah et al, 2019), we consider Tobin's Q as a market-based measure of firm performance for the robustness test. The findings shown in R&D_S, R&D_A, and R&D_C adversely influence firm performance.…”
Section: Robustness Testsmentioning
confidence: 99%
“…Rewards and recognition have also been found to be critical factors in the enhancement of employee engagement, morale, motivation and satisfaction (Mone and London, 2010; Alhmoud and Rjoub, 2020). Employees who are not compensated or rewarded fairly are likely to experience a lower level of work motivation or even engage in expropriating firm resources for their personal benefits (Ferry et al , 2021). Similarly, lack of the right recognition program could lead to employee burnout, which is the opposite of engagement (Maslach et al , 2001), This could cause the devaluation of employees’ work, leading to a feeling of inefficacy (Cordes and Dougherty, 1993), and thereby, a high turnover rate (Younies and Al-Tawil, 2021).…”
Section: Related Literature and Hypotheses Developmentmentioning
confidence: 99%